A review of behavioural measures and research methodology in sport and exercise psychology - Meredith, S. J.; Dicks, M.; Noel, B.; Wagstaff, C. R. D. (International Review of Sport and Exercise Psychology, 2018)
This study examined the development of methodologies and measures used in sport and exercise psychology (SEP) publications between 1979 and 2013. A systematic coding process was conducted on a total of 1377 manuscripts sampled from four long-standing SEP publications, namely Journal of Applied Sports Psychology, Journal of Sport and Exercise Psychology, Psychology of Sport and Exercise, and The Sport Psychologist. Analyses compared the type of behavioural or non-behavioural measures used, and the research design employed. Findings suggested that overall SEP has included more behavioural measures in comparison to other psychology domains, and there has been substantial sampling of sport and exercise behaviours using direct rather than indirect behavioural measures. Nevertheless, proportions of dependent behavioural measures in SEP were significantly less than non-behavioural measures. Questionnaires have remained a dominant non-behavioural measure over time, and higher proportions of SEP studies were conducted within a semi-natural social setting. Findings are discussed in line with SEP practice, and the potential implications for future works.